2020
DOI: 10.1002/jrs.5820
|View full text |Cite
|
Sign up to set email alerts
|

In situ and ex situ surface‐enhanced Raman spectroscopy (SERS) analysis of cell mitochondria

Abstract: As the "powerhouse" of cells, mitochondrion is the main site of cellular aerobic respiration and plays a vital role in performing many important cellular functions. The consequence of mitochondrial dysfunction could lead to a wide range of disorders and diseases. Traditional mitochondria‐related cytobiology methods always require the isolation of organelles for biological components, followed by structural analysis and quantitative analysis. In this study, we tried to assess the feasibility and reliability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Hence, the relative lipid/carbohydrate level is a factor related to σ (ω, ω ′ ) over the capacitive and resistive behaviour of the cell membrane. Therefore, based on the published Raman spectra for BT-474, MCF-7 and lymphocytes [55][56][57], the approximate lipid-to-carbohydrate ratios were extracted, as summarized in table 1. The overall capacitance, C p , is proportional to the lipid-to-carbohydrate integrated Raman vibrational ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the relative lipid/carbohydrate level is a factor related to σ (ω, ω ′ ) over the capacitive and resistive behaviour of the cell membrane. Therefore, based on the published Raman spectra for BT-474, MCF-7 and lymphocytes [55][56][57], the approximate lipid-to-carbohydrate ratios were extracted, as summarized in table 1. The overall capacitance, C p , is proportional to the lipid-to-carbohydrate integrated Raman vibrational ratios.…”
Section: Resultsmentioning
confidence: 99%
“…[ 101 ] Future in vivo studies are expected to require highly efficient data processing and analysis, which can be provided by ML algorithms. [ 102 ] To further enhance the efficiency and robustness, automation of data collection and filtering for large‐sample‐set biological studies will be highly desired. [ 103 ]…”
Section: Discussionmentioning
confidence: 99%
“…They found that the AuNPs did not cause significant damage to mitochondria 100 . Besides, Xu's group investigated the molecular information of mitochondria from cancer cells in situ with the assistant of mitochondrion-targeting nanoprobes, compared with the isolation-based ex situ method 120 . In the following study, Xu et al investigated the dynamic molecular changes of the extracted living mitochondria upon phototherapy by SERS, to elucidate the underlying molecular mechanisms associated with cell death induced by subcellular dysfunction.…”
Section: Subcellular Compartment Sers Detectionsmentioning
confidence: 99%